The Making of Authentic Deeds by Notaries Without the Presence of the Parties During the Covid 19 Virus Pandemic - Pratama, Satria Bagas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Notaries are authorized by law to make authentic deeds. When presenting their wishes, they are required to appear before a Notary as stated in Article 38 paragraph (3) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. However, at the beginning of 2020, Indonesia was hit by the spread of the Covid-19 virus, which prompted the government to carry out large and small scale efforts in all sectors. This influence affects the notary's performance in carrying out his duties and powers. The cyber notary concept has become an alternative method during the Covid-19 pandemic. The absence of the parties to appear has affected the strength of the notarial deed. This research method is normative with secondary data sources using primary, secondary and tertiary legal materials. A notarial deed made without a presenter has the power of a private deed, but can be upgraded to an authentic deed when the presenter comes before the notary, signed by the notary, the parties and the witness.